Tradisi Tutur Lisan Dongeng di Era Digital oleh Orangtua Terhadap Anak di Kampung Kaum Kabupaten Cianjur - Rahmat Arifpin Nugraha (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
The tradition of storytelling is one of the local wisdoms that serves to convey moral messages by parents to children through fairy tales. The existence of fairy tales in the digital era  is a challenge for parents to tell as part of the preservation of moral and cultural values. Because digital tales are able to present interesting visuals for children. This study aims to analyze how the continuity of the tradition of oral fable speech in the digital era by parents of the children under the age of 11 in Kampung Kaum Cianjur. The method used is a combination. The sampling technique uses saturated sampling. The result of this study indicated that the tradition of storytelling in Kampung Kaum Cianjur is still going well. This can be seen from the answers of parents who are still doing of storytelling as much as 74% and parents have no difficulty when storytelling as much as 86%. 93% of parents in Kampung Kaum Cianjur still recognize the typical Cianjur tales such as the myth of the Kuda Kosong, Eyang Suryakancana, and Pangguyangan Badak Putih, even though most parents said they had rarely told Cianjur tales compared to other popular tales.